ATTRIBUTES OF A GOOD MEDICAL SCHOOL: FACULTY PERSPECTIVE IN LOCAL CONTEXT - Ali, Asif; Habib, Syed Hamid; Shah, Inayat; Jan, Amin; Yousafzai, Yasar Mehmood (Pakistan Journal of Physiology, 2017)
Background: Medical schools and institutions are required to meet the standards of national and international accreditation bodies. These standards guide the attributes of a good medical school. The current study was designed to identify the attributes of a good medical school from a local perspective. Methods: For this qualitative study based upon grounded theory, 25 participants were recruited through purposive sampling who underwent a workshop to get an insight about the attributes of a good medical school. They were asked to provide the faculty perspectives of a good medical school. The participant responses were put in online software ‘Worditout’ to look for the repetitions of words, followed by open coding technique. Initial coding was followed by a second phase of axial coding of the data in order to identify themes and thematic analyses of all the data were performed. Results: The teaching experience of the participants in medical schools varied from 2 to 20 years. In total, 198 responses/comments from all the participants were recorded. After doing the open and axial coding all the responses were summarized into four themes. The themes highlighted in order of the response frequency were: 1) improved learning strategies and opportunities; 2) modification and improvements in teaching methodologies; 3) standardised and programmatic assessment methods and 4) parameters of quality assurance and management. Conclusion: The attributes of a good medical school are guided by the national and international standards. However, some of the standards are contextual and our study showed these standards as attributes of a good medical school. It includes provision of better learning opportunities, teaching methodologies, standardised assessment and quality assurance. Pak J Physiol 2017;13(4):48–51